2016
DOI: 10.1089/ars.2016.6661
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Transient Receptor Potential 6 Channel: A New Target of Reactive Oxygen Species in Renal Physiology and Pathology

Abstract: Significance: Regulation of Ca 2+ signaling cascade by reactive oxygen species (ROS) is becoming increasingly evident and this regulation represents a key mechanism for control of many fundamental cellular functions. Canonical transient receptor potential (TRPC) 6, a member of Ca 2+ -conductive channel in the TRPC family, is widely expressed in kidney cells, including glomerular mesangial cells, podocytes, tubular epithelial cells, and vascular myocytes in renal microvasculature. Both overproduction of ROS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 236 publications
(130 reference statements)
0
41
0
Order By: Relevance
“…We previously reported that TRPC6 channels contribute to LPSinduced inflammatory response in human bronchial epithelial cells, which implies that TRPC6 may be a therapeutic target in bronchial epithelial inflammation 36 . It has been well described in many cell types and tissues that the activity of TRPC6 channel is redox-sensitive, while it seems to have different phenotype according to different cell types 23,37 . In podocytes, HEK 293T cells and vascular myocytes, ROS not only activates TRPC6 already in the plasma membrane but also upregulates the expression of TRPC6 in the surface [38][39][40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that TRPC6 channels contribute to LPSinduced inflammatory response in human bronchial epithelial cells, which implies that TRPC6 may be a therapeutic target in bronchial epithelial inflammation 36 . It has been well described in many cell types and tissues that the activity of TRPC6 channel is redox-sensitive, while it seems to have different phenotype according to different cell types 23,37 . In podocytes, HEK 293T cells and vascular myocytes, ROS not only activates TRPC6 already in the plasma membrane but also upregulates the expression of TRPC6 in the surface [38][39][40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…After the activation of TLR4 and generation of DAG, TRPC6-dependent Ca 2+ influx into endothelial cells is triggered and cooperated in endotoxin-induced lung inflammation 19 . Moreover, growing evidence points out that TRPC6 acts as a redoxrelated channel, while the definite relation between TRPC6 and ROS seems to be affected by cell specific difference [20][21][22][23] . Recently, we reported that TRPC6 is a key element in the regulation of adhesion of neutrophils to bronchial epithelial cell with O 3 exposure 24 , while the role and regulatory mechanisms of TRPC6 channel in oxidative stress-induced airway inflammation are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The application of alprostadil combined with calcium dobesilate in patients with diabetic nephropathy can more efficiently reduce the microvascular wall permeability, decrease the whole blood viscosity, and inhibit the platelet aggregation ( 11 13 ). These effects significantly alleviate the clinical symptoms, reducing small molecule proteins from blood, and improving renal functions ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the conflicting results, the mechanisms of hyperforin on TRPC6 are not fully understood and its effect on the channel seems cell specific and different from antioxidant effect on TRPM2 and TRPV1 in sciatic nerve and DRG neurons. Results of recent studies indicate role of oxidative stress on the activation of TRPC6 in kidney cells (Zhao et al, 2015;Ma et al, 2016), although there is no report on oxidative stressdependent activation of TRPC6 in brain and neurons. The subject should be clarified by future studies.…”
Section: In Conclusion and Future Directionsmentioning
confidence: 99%